THE EXISTENCE OF COASTAL FOREST, ITS IMPLICATION FOR TSUNAMI HAZARD PROTECTION, A CASE STUDY: IN CILACAP-CENTRAL JAVA, INDONESIA - Yudhicara Yudhicara (Bulletin of the Marine Geology, 2017)
The southern coast of Java which is facing to the Indian Ocean has many of natural hazard potential come from the sea. Since 2006 tsunami impacted the southern coast of Java, and caused severely damage especially along the coast of Cilacap (1-7,7 m run up height). People commit to do greening the beach by planting suitable plants such as a Casuarina equisetifolia, Terminalia catappa, and Cocos nucifera. This paper discusses the existence of coastal forests in Cilacap coastal area, their potential ability as a coastal protection from the tsunami wave which cover the density, diameter, height, age, and other parameters that affects the coastal defence against tsunami waves. Some experiences of tsunamis that have occurred, indicating that the above parameters linked to the ability of vegetation to act as a natural barrier against tsunamis. In the case of sandy beaches, such as in Cilacap, Pandanus odorarissimus has more effectiveness than other trees due to its hanging roots that can withstand the tsunami height less than 5 m, able to withstand debris and can withstand the scouring effects of tsunami waves, while Casuarina equisetifolia along Cilacap beaches more dominant than other trees, so it is recommended to increase the diversity of plants as well as increase the density and tree placement setting. By field measurement in order to get parameter applied to some graphs, Cilacap coastal forest does not enough capability for tsunami barrier reflected to the tsunami height experience in this region. Ages could be the important parameter in order to have bigger diameter trunk, higher trees height, and high resistance capacity againts tsunami hazard potential. Compare to Kupang, East Nusa Tenggara, Cilacap coastal forest still young and need some more years to make trees ready act as tsunami reduction.